Activation of Heme Oxygenase-1 is Involved in the Preventive Effect of Honokiol against Oxidative Damage in Human Retinal Pigment Epithelial Cells - Hong, Su Hyun; Park, Cheol; Hwangbo, Hyun; Bang, EunJin; Kim, Sung Ok; Shim, Jung-Hyun; Park, Shin-Hyung; Lee, Hyesook; Leem, Sun-Hee; Kim, Gi-Young; Choi, Yung Hyun (Biotechnology and bioprocess engineering, 2022)
Previous studies have shown that honokiol, a bioactive compound originated from the Magnolia , has beneficial effects on various chronic diseases. Although our previous study has demonstrated that honokiol effectively protects C2C12 myoblasts against hydrogen peroxide (H 2 O 2 )-induced oxidative stress and cytotoxicity, the antioxidant mechanism in human retinal pigment epithelial (RPE) cells has not been reported yet. Therefore, this study investigates whether honokiol attenuate cytotoxicity of H 2 O 2 to human RPE ARPE-19 cells. Our results showed that H 2 O 2 -induced loss of cell viability and increase of reactive oxygen species production in ARPE-19 cells were significantly alleviated by honokiol, which was associated with increased phosphorylation of nuclear factor erythroid 2-related factor 2 (Nrf2) and upregulation of heme oxygenase-1 (HO-1). In addition, honokiol markedly attenuated DNA damage and G2/M phase cell cycle arrest and improved apoptosis in H 2 O 2 -treated ARPE-19 cells. Furthermore, mitochondrial dysfunction by H 2 O 2 was reversed by honokiol through preservation of mitochondrial membrane potential, decrease of Bax/Bcl-2 expression ratio, and inhibition of cytochrome c release into the cytoplasm. However, zinc protoporphyrin, an inhibitor of HO-1, significantly abrogated these preventive effects, suggesting a critical role of Nrf2/HO-1 in the antioxidant activity of honokiol. Taken together, these results demonstrate that activation of Nrf2/HO-1 antioxidant signaling by honokiol could rescue ARPE-19 cells from oxidative damage.